MOLECULAR MECHANISMS AND ALGORITHMIC REALITIES: A SOCIO-MEDICAL ANALYSIS OF GLP-1 RECEPTOR AGONISTS IN THE CONTEXT OF EATING DISORDER SPECTRUM - Mazurkiewicz, Weronika; Borecka, Zuzanna; Sobczak, Agnieszka; Szymczak, Alicja; Jaworowicz, Anna; Piasecka, Joanna; Gołembiewski, Bartosz; Mulski, Grzegorz; Manicka, Martyna; Baranowicz, Michał (International Journal of Innovative Technologies in Social Science, 2026)
Background: While Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are established treatments for obesity, their role in eating disorders (EDs) is a rapidly evolving frontier. This review evaluates the clinical efficacy, neurobiological mechanisms, and safety of GLP-1 RAs across binge eating disorder (BED), bulimia nervosa (BN), and anorexia nervosa (AN), while critically examining the socioeconomic and technological drivers of their recent proliferation.Methods: A systematic literature search was conducted across PubMed, Scopus, Web of Science, and the Cochrane Library in December 2025. Inclusion criteria focused on clinical trials, mechanistic studies, and pharmacovigilance reports addressing behavioral and metabolic outcomes of GLP-1 RAs.Results: Current evidence identifies BED as the primary clinical indication; meta-analyses demonstrate significant weight loss (-3.81 kg), BMI reduction (-1.48 kg/m²), and improved Binge Eating Scale scores (-8.14 points). These effects are driven by hypothalamic satiety regulation and the dampening of dopamine-mediated motivational “wanting” (incentive salience) for palatable foods. For BN, data remain exploratory. Conversely, GLP-1 RAs are discouraged in AN due to the high risk of reinforcing restrictive pathology and severe undernutrition. The review also identifies risks associated with direct-to-consumer telemedicine and social media trends like “Ozempic face”, which may bypass psychiatric screening.Conclusions: GLP-1 RAs offer significant therapeutic potential for BED with comorbid obesity but require a multidisciplinary framework to mitigate risks of unmonitored prescribing and weight stigma. Future research must prioritize long-term, disorder-specific safety data.